PENALARAN DAN OBJEKTIVITAS MORAL: FILSAFAT ETIKA AYATULLAH MUHAMMAD TAQI MISHBAH YAZDI - Sulaiman, Ahmad; Fauzi, Ammar (UIN Raden Mas Said Surakarta, 2024)
Muslim society today is experiencing an impasse in moral philosophy caused by the dominance of Ghazalian metaphysics. This especially occurs through a shallowing in the process of moral reasoning due to the endorsement that all moral values ​​are absolute conventions of God and can only be accessed exclusively through the written word and spiritual guides. As a result, Muslims tend to be blunt, passive and reactionary in dealing with social problems that are increasingly dynamic in the midst of pluralism and intensive democratization. This condition must be responded to immediately by presenting an alternative moral philosophical paradigm that can overcome the shortcomings in the dominant view available. The moral philosophical views that will be explained are those constructed by Ayatullah Muhammad Taqi Mishbah Yazdi, a great Islamic philosopher from Iran. The research method used is literature study. The research results show that his thinking places ontology as a moral foundation and harmonizes reason with revelation simultaneously. Ayatullah Yazdi's system of moral philosophy has the potential to be an important subtitute in presenting a Muslim social scientific attitude that is critical but still dialogical in facing increasingly dynamic realities.